The Effect of Storytelling Methods and Self-Confidence Children's Expressive Language Skills - Jhoni Warmansyah; Evi Selva Nirwana (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to determine the effect of the storytelling method and self-confidence on the expressive language skills of early childhood. The approach used is quantitative through an experimental method with treatment by level 2x2 design. This research was conducted on children in group B Kindergarten in Tanah Datar Regency. The sampling technique used is simple random sampling (simple random sampling). The number of samples in this study was 24 children (12 in the experimental class and 12 in the control class. Data collection in this study used a self-made checklist. The data analysis technique in this study used two-way ANOVA to see the main effects and interactions then used the Tukey test). To see a simple effect, the results of this study are as follows: 1) The expressive language ability of children who are given the storytelling method is higher than the children who are given the show and tell treatment. 2) There is an interaction between the storytelling method and self-confidence, in general, it has a significant effect on children's expressive language skills. 3) Children who have high self-confidence, by being treated with the storytelling method have higher expressive language skills than using the show and tell storytelling method). 4) Children who have low self-confidence using the show and tell storytelling method have higher expressive language skills than those who are treated using the storytelling method